The characteristics and reproducibility of motor speech functional neuroimaging in healthy controls - Kenyon, Katherine H.; Boonstra, Frederique; Noffs, Gustavo; Morgan, Angela T.; Vogel, Adam P.; Kolbe, Scott; Van Der Walt, Anneke (Frontiers in Human Neuroscience, 2024)
Introduction Functional magnetic resonance imaging (fMRI) can improve our understanding of neural processes subserving motor speech function. Yet its reproducibility remains unclear. This study aimed to evaluate the reproducibility of fMRI using a word repetition task across two time points. Methods Imaging data from 14 healthy controls were analysed using a multi-level general linear model. Results Significant activation was observed during the task in the right hemispheric cerebellar lobules IV-V, right putamen, and bilateral sensorimotor cortices. Activation between timepoints was found to be moderately reproducible across time in the cerebellum but not in other brain regions. Discussion Preliminary findings highlight the involvement of the cerebellum and connected cerebral regions during a motor speech task. More work is needed to determine the degree of reproducibility of speech fMRI before this could be used as a reliable marker of changes in brain activity.